Associations of early marriage and early childbearing with anemia among adolescent girls in Ethiopia: a multilevel analysis of nationwide survey - Fentanesh Nibret Tiruneh; Mesfin Wogayehu Tenagashaw; Degnet Teferi Asres; Hirut Assaye Cherie (BMC, 2021)
Abstract Background Early marriage and early childbearing are common practices in Ethiopia. Girls who get married and give birth at a very young age are more likely to experience several health problems including anemia among others. However, the effects of early marriage and early childbearing on anemia status of adolescent girls have not been quantified in previous studies. In this study, we assessed whether early marriage and early childbearing measured at both individual and community levels are associated with adolescent anemia. Methods We analyzed data from the 2016 demographic and health survey of Ethiopia. Our study focused on 3172 late female adolescents (15-19 years). We used the chi-squared test and spearman correlation coefficients for bivariate analysis. The relationship between early marriage and childbearing with anemia was evaluated using multilevel binary logistic regression models while controlling other determinants. Results Overall prevalence of anemia among female adolescents was 23.8% (95% CI; 22.3-25.2). Our multivariable multilevel analysis showed that individual-level marital status (AOR = 1.53, 95% CI = 1.06-2.02) and community-level childbearing status (AOR = 2.80, 95% CI 1.25-6.29) were positively associated with anemia among female adolescents. Conclusion Our findings show the presence of significant association between early marriage & early childbearing with adolescent anemia. Therefore, there is a need for effective policies and programs to end the practice of early child marriage and the consequent adolescent pregnancy in Ethiopia. This will help to improve nutritional status of adolescent girls as well as nutritional outcomes of their children.